Sustainable Synthesis of Magnetic Nanoparticles Through Green Chemistry - Mohamad Rojie, Muhammad Izwan Hafifi; Mohamad Hakimi, Nurul Asyikin; Abd Ghani, Muhammad Hilman Daniel; Mohd Zuhan, Mohd Khairul Nizam (Multidisciplinary Applied Research and Innovation, 2025)
Because they are sustainable, developing green chemistry techniques for producing metal nanoparticles is an important area of research. This work explores the effects of temperature and reducing agent concentration on solution absorbance in the green production of magnetite nanoparticles using Carica papaya as a reducing agent. Smaller nanoparticles appropriate for anticorrosive coatings were created by the procedure using co-precipitation at different temperatures. The study also investigates the use of plant extracts, which include biomolecules like proteins, amino acids, polysaccharides, and flavonoids, to produce iron nanoparticles quickly, cheaply, and without pathogenicity. By assisting in the decrease and stabilization of iron ions, these biomolecules guarantee the stability of nanoparticles. Advanced characterisation methods were used to examine the structural characteristics, surface morphology, and functional groups of the nanoparticles, including Energy-Dispersive X-ray Spectroscopy (EDX), Scanning Electron Microscopy (SEM), and Fourier Transform Infrared Spectroscopy (FTIR). The results demonstrate the special qualities of Fe3O4 nanoparticles, which make them safe for usage by humans, including their strong paramagnetism and biodegradability. This work emphasizes on environmental sustainability and technical developments, highlighting the promise of green synthesis methods for generating metal nanoparticles with a variety of industrial uses.